Whole-exome sequencing identifies mutations in the nucleoside transporter gene SLC29A3 in dysosteosclerosis, a form of osteopetrosis - Campeau, Philippe M. (Oxford University Press, 2012)
Dysosteosclerosis (DSS) is the form of osteopetrosis distinguished by the presence of skin findings such as red-violet macular atrophy, platyspondyly and metaphyseal osteosclerosis with relative radiolucency of widened diaphyses. At the histopathological level, there is a paucity of osteoclasts when the disease presents. In two patients with DSS, we identified homozygous or compound heterozygous missense mutations in SLC29A3 by whole-exome sequencing. This gene encodes a nucleoside transporter, mutations in which cause histiocytosis–lymphadenopathy plus syndrome, a group of conditions with little or no skeletal involvement. This transporter is essential for lysosomal function in mice. We demonstrate the expression of Slc29a3 in mouse osteoclasts in vivo. In monocytes from patients with DSS, we observed reduced osteoclast differentiation and function (demineralization of calcium surface). Our report highlights the pleomorphic consequences of dysfunction of this nucleoside transporter, and importantly suggests a new mechanism for the control of osteoclast differentiation and function.